EP498 Oncologic and pregnancy outcomes with fertility-sparing management for early endometrial cancer in young women. (1st November 2019) - Chung, YS; Lee, J-Y; Nam, EJ; Kim, S; Kim, SW; Kim, YT
Abstract : Introduction/Background: This study evaluated the oncologic and pregnancy outcomes of progestin treatment for early endometrial cancer in young women. Methodology: We retrospectively analyzed the medical records of 82 patients younger than 45 years with early stage endometrial cancer who had received fertility-sparing management between 2006 and 2018. All of the patients were treated with medroxyprogesterone acetate (MPA) or megestrol acetate (MA) or combined MPA/levonorgestrel-intrauterine system (LNG-IUS). Results: Fifty-nine patients (72.0%) showed complete response (CR) after progestin therapy, and 19 (32.2%) of them experienced recurrence after median follow-up time of 29.2 months. Age ≥35 (p=0.011), body mass index (BMI) ≥25 (p=0.015), and myometrial invasion (p=0.002) were significantly negative factors associated with achieving CR. Multivariate analysis showed that myometrial invasion (hazard ratio [HR]=14.00, 95% confidence interval [CI] 2.45–80.14, p=0.003) was significantly associated with a higher risk of recurrence and maintenance treatment (HR=0.26, 95% CI 0.08–0.85, p=0.026), and assisted reproductive technology (ART) utilization (HR=0.20, 95% CI 0.06–0.66, p=0.008) were significantly associated with a lower risk of recurrence. Of the 24 (40.7%) patients who tried to conceive after CR, 21 (87.5%) patients underwent ART, 12 (50.0%) patients experienced pregnancy, 9 patients (75.0%) had live newborn infants. Conclusion: Fertility-sparing management for early endometrial cancer with progestin is significantly effective. Patients with maintenance treatment, ART utilization, and without myometrial invasion associated with a higher probability of long-term success. Disclosure: Nothing to disclose.